Climate change impacts on cocoa in Ghana: Presentation at CCAFS Stakeholder Workshop - Accra, Ghana - Bunn, Christian (2016)
What is the projected impact of climate change on cocoa value chains in Ghana? What can be done to improve the resilience of these production systems to the projected impact of climate change?